Luminosity monitoring and calibration of BLM - 薛镇 许咨宗 汪晓莲 胡涛 王至勇 傅成栋 鄢文标 吕军光 周莉 蔡啸 俞伯祥 方建 孙希磊 石峰 王志刚 交正华 孙丽君 刘宏邦 章爱武 王晓东 (Chinese physics C, 2011)
The BEPC II Luminosity Monitor （BLM） monitors relative luminosity per bunch. The counting rates of gamma photons, which are proportional to the luminosities from the BLM at the center of mass system energy of the φ（3770） resonance, are obtained with a statistical error of 0.01% and a systematic error of 4.1%. Absolute luminosities are also determined by the BESIII End-cap Electro-Magnetic Calorimeter （EEMC） using Bhabha events with a statistical error of 2.3% and a systematic error of 3.5%. The calibration constant between the luminosities obtained with the EEMC and the counting rates of the BLM are found to be 0.84±0.03 （×10^26 cm^-2-count^-1）. With the calibration constaat, the counting rates of the BLM can be scaled up to absolute luminosities.